Edukasi kesehatan berbasis influencer media sosial untuk meningkatkan perilaku pencegahan infeksi saluran reproduksi pada remaja - Meriem Meisyaroh Syamson; Nasrayanti Nurdin; Cakrawardi Syawal; Faridah Faridah; Handayani Handayani (JOURNAL of Public Health Concerns, 2026)
Background: Reproductive tract infections (RTIs) are a health issue among adolescents that warrants attention due to their potential long-term impact on reproductive health. Limited knowledge, a lack of access to accurate information, and the strong influence of social media on adolescent behavior serve as key reasons for conducting this community service activity. Purpose: To improve adolescents' knowledge and preventive behaviors regarding reproductive tract infections through health education facilitated by social media influencers. Method: This community service activity employed a participatory, social media-based educational approach and was conducted at SMP 1 Watang Pulu, Sidenreng Rappang Regency, on May 18, 2026. The activity involved 50 female students as participants and two local influencers as facilitators. The goal was to foster an understanding of RTI prevention, particularly among adolescents who are highly engaged with digital and social media. Evaluation was carried out through simple Q&A sessions, observation of participant engagement during discussions, and feedback regarding the presented material and social media content. Descriptive evaluation results were used to assess the extent to which the educational activity improved adolescents' knowledge regarding RTI prevention. Results: The results demonstrated an improved understanding among adolescents regarding the importance of maintaining reproductive health, as well as heightened awareness of the need to adopt behaviors that prevent reproductive tract infections. Improvements in knowledge covered the definition of reproductive tract infections, risk factors, warning signs and symptoms, and the consequences of the excessive use of reproductive hygiene products. Participants also demonstrated awareness regarding the adoption of clean and healthy living practices related to reproductive health. Conclusion: Educational activities combining direct outreach, interactive discussions, and digital campaigns involving influencers proved effective in enhancing adolescents' knowledge of reproductive health. Delivering information through an adaptive and engaging approach leveraging local social media influencers fostered awareness among the adolescent community regarding the adoption of behaviors to prevent reproductive tract infections (RTIs) in their daily lives. The involvement of local social media influencers serves as a highly relevant health promotion strategy for shaping community character and encouraging healthy lifestyles. Suggestion: Adolescent reproductive health education initiatives should be conducted regularly and sustainably by fostering strong synergy among schools, families, communities, and healthcare professionals. Local social media influencers participating in health promotion programs should receive health-related briefings to ensure that the digital content they produce is not only well-received by the public but also aligns with ethical standards and health principles. Keywords: Adolescents; Influencers; Preventive behaviour; Reproductive tract infections; Social media Pendahuluan: Infeksi saluran reproduksi merupakan salah satu masalah kesehatan remaja yang perlu mendapat perhatian karena dapat berdampak pada kesehatan reproduksi jangka panjang. Rendahnya pengetahuan, kurangnya akses informasi yang benar, serta kuatnya pengaruh media sosial terhadap perilaku remaja menjadi alasan penting dilakukannya kegiatan pengabdian masyarakat ini. Tujuan: Untuk meningkatkan pengetahuan dan perilaku pencegahan infeksi saluran reproduksi pada remaja melalui edukasi kesehatan berbasis influencer media sosial. Metode: Pelaksanaan kegiatan pengabdian masyarakat ini menggunakan pendekatan edukasi partisipatif berbasis media sosial yang dilaksanakan di sekolah SMP 1 Watang Pulu Kabupaten Sidenreng Rappang pada tanggal 18 Mei 2026. Melibatkan 50 siswi untuk menjadi partisipan dan 2 orang influencer lokal untuk menjadi fasilitator kegiatan. Sasaran kegiatan ini adalah memberikan pemahaman tentang pencegahan infeksi saluran reproduksi khususnya pada remaja yang memiliki kedekatan tinggi dengan media digital atau media sosial. Evaluasi dilakukan melalui tanya jawab sederhana, observasi keaktifan peserta saat diskusi, serta tanggapan peserta terhadap materi dan konten media sosial yang disampaikan. Hasil evaluasi deskriptif digunakan untuk melihat sejauh mana kegiatan edukasi mampu meningkatkan pengetahuan remaja mengenai pencegahan infeksi saluran reproduksi. Hasil: Menunjukkan adanya peningkatan pemahaman remaja mengenai pentingnya menjaga kesehatan reproduksi serta meningkatnya kesadaran untuk menerapkan perilaku pencegahan infeksi saluran reproduksi. Peningkatan aspek pengetahuan meliputi pengertian infeksi saluran reproduksi, faktor risiko terjadinya infeksi saluran reproduksi, tanda dan gejala yang perlu diwaspadai, dan dampak dari penggunaan produk pembersih organ reproduksi secara berlebihan. Menunjukkan kesadaran tentang penerapan perilaku hidup bersih dan sehat terkait kesehatan reproduksi. Simpulan: Kegiatan edukasi menggabungkan penyuluhan langsung, diskusi interaktif, dan kampanye digital melalui keterlibatan influencer terbukti efektif dalam meningkatkan pengetahuan tentang kesehatan reproduksi bagi remaja. Penyampaian informasi melalui pendekatan yang adaptif dan menarik melalui influencer media sosial lokal menumbuhkan kesadaran komunitas remaja untuk menerapkan perilaku pencegahan infeksi saluran reproduksi (ISR) dalam kehidupan sehari-hari. Keterlibatan influencer media sosial lokal menjadi strategi promosi kesehatan yang sangat relevan dalam membangun karakter masyarakat dalam menerapkan pola hidup sehat. Saran: Kegiatan edukasi kesehatan reproduksi remaja sebaiknya dilaksanakan secara berkala dan berkelanjutan dengan membangun sinergi yang kuat antara pihak sekolah, keluarga, komunitas, serta tenaga kesehatan. Influencer media sosial lokal yang dilibatkan dalam program promosi kesehatan perlu diberikan pembekalan tentang kesehatan agar konten digital yang diproduksi semakin mudah untuk diterima masyarakat tetap sesuai etika dan prinsip kesehatan.